Economic impact of medication error: a systematic review†. Issue 5 (13th March 2017) - Walsh, Elaine K.; Hansen, Christina Raae; Sahm, Laura J.; Kearney, Patricia M.; Doherty, Edel; Bradley, Colin P.
Abstract: Purpose: Medication error is a significant source of morbidity and mortality among patients. Clinical and cost‐effectiveness evidence are required for the implementation of quality of care interventions. Reduction of error‐related cost is a key potential benefit of interventions addressing medication error. The aim of this review was to describe and quantify the economic burden associated with medication error. Methods: PubMed, Cochrane, Embase, CINAHL, EconLit, ABI/INFORM, Business Source Complete were searched. Studies published 2004–2016 assessing the economic impact of medication error were included. Cost values were expressed in Euro 2015. A narrative synthesis was performed. Results: A total of 4572 articles were identified from database searching, and 16 were included in the review. One study met all applicable quality criteria. Fifteen studies expressed economic impact in monetary terms. Mean cost per error per study ranged from €2.58 to €111 727.08. Healthcare costs were used to measure economic impact in 15 of the included studies with one study measuring litigation costs. Four studies included costs incurred in primary care with the remaining 12 measuring hospital costs. Five studies looked at general medication error in a general population with 11 studies reporting the economic impact of an individual type of medication error or error within a specific patient population. Conclusions: Considerable variability existed between studies in terms of financial cost, patients, settings and errors included. Many were of poor quality. Assessment of economic impact was conducted predominantly in the hospital setting with little assessment of primary care impact. Limited parameters were used to establish economic impact. Copyright © 2017 John Wiley & Sons, Ltd.